2018
DOI: 10.1590/18069657rbcs20170199
|View full text |Cite
|
Sign up to set email alerts
|

Soil Biological, Chemical, and Physical Properties After a Wildfire Event in a Eucalyptus Forest in the Pampa Biome

Abstract: Wildfire events cause considerable environmental disturbance but few studies have examined changes in soil properties due to fire. This study aimed to assess the effect of a wildfire event on chemical, physical, and biological properties of the soil in a eucalyptus forest in the Pampa biome. Part of a seven-year-old eucalyptus forest was affected by a wildfire event that lasted for two days. Soil and plant litter sampling was performed in three areas: in the forest that was not affected by the fire, in the for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 41 publications
0
9
0
1
Order By: Relevance
“…pH increases significantly only if burning occurs at high temperatures to achieve complete combustion of vegetative residues ( Arocena and Opio, 2003 ). The non-replenishment of organic materials would also be responsible for the low pH in the FP since less alkaline cations could be released during burning ( Santana et al., 2018 ). There is a positive correlation between pH and SOM ( Chungu et al., 2019 ); therefore, with the decreasing SOM in FP, pH would not be expected to increase even after occasional burning.…”
Section: Discussionmentioning
confidence: 99%
“…pH increases significantly only if burning occurs at high temperatures to achieve complete combustion of vegetative residues ( Arocena and Opio, 2003 ). The non-replenishment of organic materials would also be responsible for the low pH in the FP since less alkaline cations could be released during burning ( Santana et al., 2018 ). There is a positive correlation between pH and SOM ( Chungu et al., 2019 ); therefore, with the decreasing SOM in FP, pH would not be expected to increase even after occasional burning.…”
Section: Discussionmentioning
confidence: 99%
“…and Mg 2? (Certini 2005;Santana et al 2018). A significant increase in pH as a result of burning occurs only at high temperatures as a result of the complete combustion of vegetative residues and is well correlated with concentrations of Ca 2?…”
Section: Bulk Density Ph and Organic Mattermentioning
confidence: 97%
“…The slashand-burn system for cropping maize and black beans in Southern Brazil was shown no effect on soil organic matter, however, the stability of soil aggregates increased when compared to unburned soil (39). Post-fire was increased the main soil nutrients, such as Ca, Mg, K and CEC (38), but soil pH, Al and Mn were decreased after a month of the fire, and no changes were found in the level of Na, Fe and Zn, therefore, it was suggested that the low fire severity have no negative impact on soil properties (32,34). Soil pH and fire severity are the key drives of fungal composition, total fungal, mycorrhizal, and saprotroph were higher in boreal forests of western Canada after an event of low fire severity and low pH (12).…”
Section: Introductionmentioning
confidence: 93%
“…Soil pH and fire severity are the key drives of fungal composition, total fungal, mycorrhizal, and saprotroph were higher in boreal forests of western Canada after an event of low fire severity and low pH (12). Low activity of some soil organisms was found due to the wildfires, which was suggested that wildfire modify soil chemical and biological properties (14,38). The action of heat modifies the soil chemical and physical status (45) and thus alterations in microbial populations may be expected following soil burning.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation